The indispensability of methyltransferase-like 3 in the immune system: from maintaining homeostasis to driving function - Zhang, Mingfu; Gou, Zhixian; Qu, Yi; Su, Xiaojuan (Frontiers in Immunology, 2024)
Methyltransferase-like 3(METTL3), recognized as the primary N 6 -methyladenosine methyltransferase, influences cellular functions such as proliferation, migration, invasion, differentiation, and fate determination by regulating gene expression post-transcriptionally. Recent studies have highlighted the indispensability of METTL3 in various immune cells such as hematopoietic stem/progenitor cells, innate immune cells (monocytes, macrophages, dendritic cells), and adaptive immune cells (thymic epithelial cell, T cells, natural killer cells). However, a comprehensive summary and analysis of these findings to elucidate the relationship between METTL3 and the immune system is yet to be undertaken. Therefore, in this review, we systematically collate reports detailing the mechanism underlying the role of METTL3 in regulating various immune processes and examine the modification of METTL3 and its potential implications. This review suggests that METTL3 plays an essential role in the immune system, ranging from maintaining homeostasis to regulating functions. Collectively, this review provides a comprehensive analysis of the relationship between METTL3 and the immune system, serving convenient researchers to understand the frontiers of immunological research and facilitate future clinical applications.